Supply Chain Management of Operational Value-at-Risk for Estimating the Maximum Claims Potential of House Fire Risk Using a Portfolio Approach - Hasbullah, Endang Soeryana; Sukono, Sukono; Suyudi, Mochammad; Agung, Moch Panji; Saepulrohman, Asep (ExcelingTech, 2020)
The occurrence of house fires in densely populated areas has a high-risk level. One of city in Indonesia that has high-risk level of this incident is Bandung City. That high-risk incident cause anxiety community, and also cause many house fire insurance product arise. Insurance product is made to protect consumers from risk and guarantee by a premium. Insurance company formulate premium based on analysis calculation from expected claim, cost, commission, and margin. This paper aims to estimate maximum expected claim using portfolio approach. There are several steps in this research. The first step is resampling the data used Maximum Entropy Bootstrapping (ME Boot). Next, determine threshold value to get extreme data value. Then, conduct Kolmogorov-Smirnov test to fit the data with Generalized Pareto Distribution (GPD). Afterwards, estimate Generalized Pareto Distribution (GPD) parameter. Then, calculate Operational Value-at-Risk (OpVaR Portfolio) as maximum expected claim measurement. The results from this research are the expected maximum claim of IDR. 18.690.352.676,615 for next one year with 95% confidence level. The expected claim result could be used as consideration for house fire insurance products premium that appropriate for Bandung City community.